2020
DOI: 10.1213/ane.0000000000004837
|View full text |Cite
|
Sign up to set email alerts
|

High-Flow Nasal Cannula Oxygen in Patients Having Anesthesia for Advanced Esophagogastroduodenoscopy: HIFLOW-ENDO, a Randomized Clinical Trial

Abstract: BACKGROUND: Over 6 million esophagogastroduodenoscopy (EGD) procedures are performed in the United States each year. Patients having anesthesia for advanced EGD procedures, such as interventional procedures, are at high risk for hypoxemia. METHODS: Our primary study aim was to evaluate whether high-flow nasal cannula (HFNC) oxygen reduces the incidence of hypoxemia during anesthesia for advanced EGD. Secondarily, we studied whether HFNC oxygen reduces h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
98
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(101 citation statements)
references
References 23 publications
1
98
2
Order By: Relevance
“…The definition of hypoxemia varied among studies. Most included hypoxemia diagnosed with SpO 2 < 90% [ 21 24 , 26 ], two studies included hypoxemia diagnosed with SpO 2 < 92% [ 27 , 28 ]. In our subgroup analysis, we included studies in which hypoxemia was defined as SpO 2 < 90%.…”
Section: Resultsmentioning
confidence: 99%
“…The definition of hypoxemia varied among studies. Most included hypoxemia diagnosed with SpO 2 < 90% [ 21 24 , 26 ], two studies included hypoxemia diagnosed with SpO 2 < 92% [ 27 , 28 ]. In our subgroup analysis, we included studies in which hypoxemia was defined as SpO 2 < 90%.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, nasal mask also significantly decreased the need for maneuvers to maintain free upper airways (8.8% vs 19.1%) and for increasing oxygen flow (15.5% vs 23.8%). The effectiveness of the nasal mask can somewhat be considered similar to the HFNC used in Mazzeffi et al 7 study. The author reported that HFNC oxygenation could reduce the incidence of hypoxemia from 33.1% to 21.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, studies with small samples reported that high-flow nasal cannula (HFNC) oxygenation and the use of a nasopharyngeal catheter could reduce the incidence of hypoxemia during anesthesia for gastroscopy. [5][6][7] However, those methods require special supplemental oxygen devices or oxygen delivery systems or they induce adverse events such as nasopharyngeal bleeding. 6,7 Therefore, it is critical to find an appropriate method to prevent hypoxemia with fewer side effects during gastroscopy.…”
mentioning
confidence: 99%
“…This may be because patients did not have their mouths closed or this is not seen in sedated patients for another reason. In procedures such as bronchoscopy [12,13], gastroscopy [14,15], endoscopic retrograde cholangiopancreatography [16] in which an improvement in oxygenation with the use of HFNT have been shown, the presence of an endoscope may have produced the same effect as having the mouth closed.…”
Section: Discussionmentioning
confidence: 99%
“…High-ow nasal oxygen (HFNT) allows the delivery of heated and humidi ed oxygen at an inspiratory fraction of oxygen (FiO 2 ) of between 0.21 to 1.0, in a ow rate of up to 60 l.min -1 [6]. Emerging evidence shows that HFNT is effective in various clinical settings such as in the treatment of acute heart failure [7][8][9], after cardiac surgery [10,11] and during procedural sedation [12][13][14][15][16][17]. Besides providing a higher degree of patient comfort by supplying warmed and humidi ed gas to maintain mucociliary functions [18], it increases pharyngeal pressure by 3 cmH 2 0 and generates an effect similar to continuous airway positive pressure (CPAP) [19].…”
Section: Introductionmentioning
confidence: 99%